Knife crime interventions: 'what works?' - Forster, Rebecca (Report, 2013)
In recent years, there has been growing concern over knife carrying and associated knife crime, in Scotland and elsewhere. Despite this increased concern, there is a lack of robust, shared knowledge on ‘what works’ in reducing knife carrying and knife crime. In light of this information dearth, a report was commissioned by the Scottish Government from the SCCJR.